1995
DOI: 10.1128/aem.61.11.3826-3831.1995
|View full text |Cite
|
Sign up to set email alerts
|

Specific PCR primers directed to identify cryI and cryIII genes within a Bacillus thuringiensis strain collection

Abstract: In this paper we describe a PCR strategy that can be used to rapidly identify Bacillus thuringiensis strains that harbor any of the known cryI or cryIII genes. Four general PCR primers which amplify DNA fragments from the known cryI or cryIII genes were selected from conserved regions. Once a strain was identified as an organism that contains a particular type of cry gene, it could be easily characterized by performing additional PCR with specific cryI and cryIII primers selected from variable regions. The met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
11

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(84 citation statements)
references
References 29 publications
3
70
0
11
Order By: Relevance
“…To date, several PCR-based methods for cry gene identification have been developed (Ceron et al 1995;Juarez-Perez et al 1997;Ben-Dov et al 1999;Song et al 2003), including specific primer PCR, multiplex PCR, exclusive PCR and PCR-RFLP. These methods directly detect known cry genes from B. thuringiensis (Ceron et al 1995;Ben-Dov et al 1999) as well as identify novel cry genes (Juarez-Perez et al 1997). In the current study, we reported the large-scale use of PCR-RFLP with a pair of novel universal primers to identify vip3A-type genes from B. thuringiensis strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several PCR-based methods for cry gene identification have been developed (Ceron et al 1995;Juarez-Perez et al 1997;Ben-Dov et al 1999;Song et al 2003), including specific primer PCR, multiplex PCR, exclusive PCR and PCR-RFLP. These methods directly detect known cry genes from B. thuringiensis (Ceron et al 1995;Ben-Dov et al 1999) as well as identify novel cry genes (Juarez-Perez et al 1997). In the current study, we reported the large-scale use of PCR-RFLP with a pair of novel universal primers to identify vip3A-type genes from B. thuringiensis strains.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of polymerase chain reaction (PCR)-based methods have been developed to detect different cry genes from B. thuringiensis strains (Ceron et al 1995;Ben-Dov et al 1999;Song et al 2003). Ce¢cile et al (2005) had described the identification of novel vip3 genes by PCR amplification using primers specific to conserved regions followed by restriction mapping of the PCR product.…”
Section: Introductionmentioning
confidence: 99%
“…The 445 isolates of B. thuringiensis were grown for 12 h at 30°C in Petri dishes with GEN nutrient medium (5 g yeast extract, 8AE8 g glucose, 10 g NaCl, 20 g agar in 1000 ml distilled water). A loop of each isolate was transferred to 100 ll sterile distilled water, the mixture was homogenized and stored at )20°C for 3 h, then immediately placed in a water bath at 100°C for 10 min to lyse the cells and finally centrifuged for 10 s at 9280 g. This supernatant was used for PCR as DNA template (Carozzi et al 1991;Ceró n et al 1994Ceró n et al , 1995Bravo et al 1998). General primers were used to characterize cry gene content (cry1, cry2, cry4 and cry11).…”
Section: Determination Of Cry Genesmentioning
confidence: 99%
“…). The conditions used for the PCR analyses were those described by Ceron et al (1994Ceron et al ( , 1995 and Bravo et al (1998). After amplification, a 15-lL aliquot of the product from each PCR reaction was electrophoresed on a 2% (w/v) agarose gel in Tris-borate buffer at 100 V for 1 h and stained with ethidium bromide.…”
Section: Dna Sample Preparation and Pcrmentioning
confidence: 99%
“…Because of their high specificity and environmental safety (Krieg and Langenbruch, 1981), Cry proteins have been successfully used as bioinsecticides against lepidopteran, dipteran, and coleopteran pests (Feitelson et al, 1992;Aranda et al, 1996;Bohorova et al, 1996). Strains with toxic activity towards nematodes (Edwards et al, 1990) and other organisms, such as platyhelminths, protozoans, prokaryotes, and acarida have been identified (Feitelson, 1994;Payne et al, 1994;Ceron et al, 1995;Yudina and Burtseva, 1997), and the activity spectrum of the toxins of B. thuringiensis is increasing as the result of the continual isolation and characterization of new strains.…”
Section: Introductionmentioning
confidence: 99%